Sex differences in neural responses to subliminal sad and happy faces in healthy individuals: Implications for depression. Issue 1 (2nd January 2017) - Victor, Teresa A.; Drevets, Wayne C.; Misaki, Masaya; Bodurka, Jerzy; Savitz, Jonathan
Abstract : Twice as many women as men suffer from mood and anxiety disorders, yet the biological underpinnings of this phenomenon have been understudied and remain unclear. We and others have shown that the hemodynamic response to subliminally presented sad or happy faces during functional MRI (fMRI) is a robust biomarker for the attentional bias toward negative information classically observed in major depression. Here we used fMRI to compare the performance of healthy females (n = 28) and healthy males (n = 28) on a backward masking task using a fast event‐related design with gradient‐recalled, echoplanar imaging with sensitivity encoding. The image data were compared across groups using a region‐of‐interest analysis with small‐volume correction to control for multiple testing ( P corrected < 0.05, cluster size ≥ 20 voxels). Notably, compared with males, females showed greater BOLD activity in the subgenual anterior cingulate cortex (sgACC) and the right hippocampus when viewing masked sad vs. masked happy faces. Furthermore, females displayed reduced BOLD activity in the right pregenual ACC and left amygdala when viewing masked happy vs. masked neutral faces. Given that we have previously reported similar findings for depressed participants compared with healthy controls (regardless of gender), our results raise the possibility that on average healthy females show subtle emotional processing biases that conceivably reflect a subgroup of women predisposed to depression. Nevertheless, we note that the differences between males and females were small and derived from region‐of‐interest rather than voxelwise analyses. © 2016 Wiley Periodicals, Inc. Abstract : Regional differences in hemodynamic response between males and females while viewing emotionally expressive face stimuli presented below the level of conscious awareness using the backward masking task.